2005
DOI: 10.2106/jbjs.d.02200
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Juvenile Rheumatoid Arthritis

Abstract: Good results, in terms of pain relief and restoration of function, were seen at a minimum of twelve years following total knee arthroplasty in our series of patients with juvenile rheumatoid arthritis. This procedure is a reasonable option when nonoperative therapy has been inadequate for patients with severe disability and pain in this relatively young population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
1
11
0
3
Order By: Relevance
“…Benefits of TKA in patients with JRA have been documented [4,7,8,26,29], but our study quantifies satisfaction and quality of life after TKA in different domains of daily life. Palmer et al [23] reported on eight patients undergoing TKA with a mean followup of 15.5 years, and three of 15 TKAs were rated as unsuccessful. Parvizi et al [24] reported on 13 patients undergoing TKA with a mean followup of 10.7 years, and Thomas et al [33] reported on 10 patients undergoing TKA with a mean followup of 6 years, but these studies did not comment on patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benefits of TKA in patients with JRA have been documented [4,7,8,26,29], but our study quantifies satisfaction and quality of life after TKA in different domains of daily life. Palmer et al [23] reported on eight patients undergoing TKA with a mean followup of 15.5 years, and three of 15 TKAs were rated as unsuccessful. Parvizi et al [24] reported on 13 patients undergoing TKA with a mean followup of 10.7 years, and Thomas et al [33] reported on 10 patients undergoing TKA with a mean followup of 6 years, but these studies did not comment on patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported an improvement in range of motion. Boublik et al [4] reported a mean flexion arc improvement of 26°, with a mean postoperative flexion arc of 103°(range, 65°-135°); Carmichael and Chaplin [8] reported a mean postoperative flexion arc of 73°(range, 15°-120°), with a mean residual flexion contracture of 17°; Thomas et al [33] reported a mean flexion arc improvement of 33°, with a mean residual flexion contracture of 7°; and Palmer et al [23] reported a 43°increase in mean arc of motion (range, 36°-79°). However, Parvizi et al [24] reported TKA did not increase range of motion in a series of 15 patients younger than 20 years who underwent TKA, and Stuart and Rand [32] reported a modest decrease in knee flexion after TKA in 26 patients (44 knees) younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Although TKA is typically performed on adult patients, it is also utilized to treat pediatric diseases affecting the knee joint such as childhood osteosarcoma, advanced juvenile rheumatoid arthritis (JRA), and osteoarthritis. [6][7][8][9][10][11][12] Despite high rates of complications and increased likelihood of revision in the younger population, the procedure has high success rates in providing pain relief, increasing joint function and improving quality of life for those who suffer from degenerative knee disorders. [9,[13][14][15][16] The incidence of primary TKA in the US population has increased between 1990 and 2002 from 129,000 to 381,000.…”
Section: Introductionmentioning
confidence: 99%